ANALISIS SISTEM AKUNTANSI DAN PROSEDUR PEMBAYARAN KLAIM JAMINAN KEMATIAN PADA PT. TASPEN (PERSERO) CABANG MANADO - Dady, Fransher; Ilat, Ventje; Pontoh, Winston (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Insurance is one of the institutions that have an important role, because its activities play a role in risk protection, raising public funds from premium revenue. Guaranteed death (JKM) is one of the insurance that acts as a protection against the risk of death due to illness or work accidents in the form of death benefit. This study aims to determine the cash accounting system cash disbursements and payment procedures Claim for death (JKM) Â applied by PT. Taspen (Persero) Manado Branch Office. Type of research used in this research is descriptive research type qualitative approach. The results showed that the accounting system and payment procedures for death insurance claim applied to PT. Taspen (Persero) Manado Branch Office has been effective because it has been in accordance with the theory of cash accounting system expenditure, by comparing the cash accounting system expenditure applied by PT. Taspen (Persero) Branch Manado with the theory of cash accounting system expenditure.Keywords: Cash Expenses, Payment Procedures, Death Warranty Claims